Análise de mutações nos genes NPM1 e IDH1 e sua associação com características clínicas e biológicas em pacientes com leucemia mielóide aguda - Nathalia Gomide Cruz (2014)
In adults patients with AML and normal karyotype, risk stratification is a challenge. In this group, mutations in the genes NPM1 and IDH1 have been analyzed for their prognostic value. This work aimed to evaluate the presence of NPM1 and IDH1 mutations in patients with AML and their association with clinical and biological features in this population. We retrospectively analyzed 149 newly diagnosed adult AML patients admitted in a single center between April 2004 and March 2013. Patients had a median age of 49 years (18 to 84 years) and 75 (50.3%) were female. In 113 (75.8%) cases AML was classified as primary and in 36 (24.2%) as secondary. The median value of WBC was 21.5 (0.5 to 380.2) x109/L and blasts was 11.0 (0.0 to 319.4) x109/L. The LDH was increased in 104/127 (81.9%) patients, and reached more than twice the upper limit of the reference range (>1,236 IU/L) in 61/127 (48.0%). The CD34 marker was positive in 52/95 (54,7%) patients. Eleven out of 119 (9.2%) patients had a favorable karyotype, 79/119 (66.4%) had a intermediate karyotype, 29/119 (24.4%) had an unfavorable karyotype and in 30/149 (20.1) karyotype was not performed. ITD-FLT3 was detected in 20/144 (13.9%) patients. Mutations in NPM1 and IDH1 were detected in 31/144 (21.5%) and 7/114 (6.1%) patients, respectively. In the normal karyotype group these mutations were observed in 9/56 (16.1), 18/55 (32.7%) and 5/46 (10.9%) patients, respectively. There was an association between mutations in NPM1 and intermediate risk group (p = 0.02), presence of normal karyotype (p < 0.01), absence of CD34 marker (p < 0.01) elevated leukocyte counts (p < 0.01) and blasts in peripheral blood (p < 0.01), serum enzyme LDH > 618 IU /L (p = 0.01) and ITD-FLT3 (p = 0.04). These associations were not observed for the IDH1 (R132) mutation. In conclusion, mutations in NPM1 were identified in a lower frequency in our population while the IDH1(R132) mutation showed a similar frequency to that described for the Caucasian population. Mutations in NPM1 were associated with prognostic factors in adult patients with AML as increased number of leukocytes and peripheral blood blasts at diagnosis, cytogenetic intermediate risk group, presence of normal karyotype and ITD-FLT3.